Nordic dual income taxation of entrepreneurs - Vesa Kanniainen; Seppo Kari; Jouko Ylä-Liedenpohja (Center for Economic Studies and ifo Institute (CESifo), 2005)
The paper shows how entrepreneurial taxes interact with the career choice of individuals, the quality of entrepreneurs, and their effort and investments. It is particularly relevant to differentiate the early effects on start-up enterprises with substantial uncertainty from the tax effects on mature firms where the uncertainty is resolved. That is why the neutrality results of dividend taxation from mature company theory do not carry over to start-up enterprises. The Nordic dual model encourages (discourages) the establishment of new enterprises by entrepreneurs who anticipate high (low) profitability.
Keywords: H25; 330; dual income taxation; enterprise taxes; Duale Einkommensteuer; Unternehmensbesteuerung; Steuerwirkung; Unternehmensgründung; Unternehmer; Berufswahl; Theorie; Nordeuropa